Preferensi Pengunjung Mahasiswa Generasi Z Masa Kini Terhadap Atribut Learning Space di Perpustakaan Akademik - Akhmadi Akhmadi; Niken Laksitarini; Ganesha Puspa Nabila (Universitas Sebelas Maret Surakarta, 2020)
Most of the current university students are born in Z Generations (1995-2010). Z Generations are unique, especially on their behavior and determining what they like. It included when they want to study around the area of their university. One of the most common study on universities is the academic library. The current academics library are also demanded to be able on adapting and presenting what Z generations want. The ideal academics library can accommodate the learning activities of this generation. This study aims to find the preferences of Z Generations in determining any learning space which come from the library. It also determining the frequency, duration, favorite floor and with whom visitor usually come to library. This preference refers to the theory of learning space attribute. The research method uses quantitative methods by using the survey and questionnaire of 185 students at the ITB, ITS and Unpad. The results showed that Z generations students agreed with the order of preference theory in learning space attribute. This means the academic librarys on university recently should refer to the theory of learning space attribute, so the library can increase the level of the visitors.